Separation, Identification, and Bioactivities of the Main Gallotannins of Red Sword Bean (Canavalia gladiata) Coats - Gan, Ren-You; Kong, Kin-Weng; Li, Hua-Bin; Wu, Kao; Ge, Ying-Ying; Chan, Chak-Lun; Shi, Xian-Ming; Corke, Harold (Frontiers in Chemistry, 2018)
The red sword bean (Canavalia gladiata) is an underutilized edible bean cultivated in China. It was previously found to have the highest content of antioxidant polyphenols among 42 edible beans, mainly gallic acid and gallotannins in its red bean coat, an apparently unique characteristic among edible beans. In this study, the main phenolic compounds in red sword bean coats were further separated by Sephadex LH-20 column chromatography, and identified by LC-MS/MS. Furthermore, the FRAP and ABTS antioxidant activities and antibacterial activity (diameter of inhibition zone, DIZ) of main gallotannin-rich fractions were tested. Our results showed that gallotannins of red sword bean coats were mainly comprised of nonogalloyl to hexagalloyl hexosides. Interestingly, tetragalloyl, pentagalloyl, and hexagalloyl hexosides were identified as the main candidates responsible for the red color of the coats. On the other hand, gallotannin-rich fractions exhibited diverse antioxidant and antibacterial activities, and tetragalloyl hexoside overall had the highest free radical scavenging and antibacterial activities. The degree of galloylation did not completely explain the structure-function relationship of gallotannins isolated from red sword bean coats, as there should exist other factors affecting their bioactivities. In conclusion, red sword bean coats are excellent natural sources of gallotannins, and their gallotannin-rich extracts can be utilized as natural antioxidant and antibacterial agents with potential health benefits as well as application in food industry.